Bio-Inspired Calix[4]arene Additives for Crystal Growth Modification of Inorganic Materials - Jones, Franca; Mocerino, Mauro; Ogden, Mark; Oliveira, Allan; Parkinson, Gordon (American Chemical Society, 2005)
Crystal growth of inorganic materials, calcium carbonate, barium sulfate and calcium oxalate, was studied in the presence of calix[4]arene additives functionalized with aspartic or glutamic acids at the lower rim. The additives were synthesized by reaction of the appropriate amino acid ester with 5,11,17,23-tetra-tert-butyl-25,-26,27,28-tetrakis(chlorocarbonylmethoxy)calix[4]arene, followed by controlled hydrolysis of the ester groups. Both additives inhibited the nucleation and growth of calcium carbonate but induced different changes in calcite morphology. The aspartic acid derivative was the more potent barium sulfate inhibitor at low concentrations, with comparable performance at higher levels. Both additives induced a polycrystalline barite precipitate. The aspartic acid functionalized calixarene also stabilized calcium oxalate dihydrate at low additive concentrations, whereas the glutamic acid derivative induced morphological changes in calcium oxalate monohydrate.